Acne Vulgaris and adherence to the mediterranean diet among university students: a case‒control study - Sari Taha; Muna Shakhshir; Sa'ed H. Zyoud (BMC, 2024)
Abstract Background Western diets, characterized by a high glycemic index and dairy content, can be risk factors for acne vulgaris. A few studies have suggested that adherence to non-Western diets, such as the Mediterranean diet (MD), may be protective against acne. This study aimed to explore the relationships between adherence to the MD and acne diagnosis and severity. Methods This was a matched case‒control study carried out among university students studying health sciences to explore the relationship between adhering to the MD and an acne diagnosis. Convenience sampling was utilized for the initial recruitment of eligible participants, who were then 1:1 individually matched for age, gender, and body mass index (BMI). Adherence to the MD was assessed using the Mediterranean Diet Adherence Screener (MEDAS) tool, and acne severity was assessed using the Global Acne Grading System (GAGS). The data were analyzed using descriptive statistics, bivariate analysis, and conditional logistic regression, which included two models based on clinical data and the backward elimination technique. Results A final sample of 121 cases was individually matched to 121 controls. Each group consisted of 28.9% males and 71.1% females, with most having a BMI within the healthy range (71.9%). Both the case (80.2%) and control groups (77.7%) demonstrated a predominant pattern of low adherence to the MD. At the bivariate level, family history significantly differed between the case and control groups (OR = 2.01, CI = 1.17-3.44), while adherence to the MD (OR = 0.86, CI = 0.46-1.60) did not reach statistical significance. According to the regression analysis, family history remained significant in the backward elimination model (aOR = 1.94, CI = 1.14-3.34), while it disappeared in the full model (aOR = 1.95, CI = 1.14-3.34). Neither model revealed a significant association between acne and the other variables. Among the participants in the case group, neither adherence to the MD nor adherence to its components was significantly associated with acne severity, except for vegetables (p = 0.022). Conclusions Adherence to the MD was not correlated with acne diagnosis or clinical severity. More research on the association between acne and adherence to the MD is needed, as earlier studies are few, were conducted in specific settings, and used variable methodologies. To improve the validity and reliability of the research methodology, the development of detailed and culturally adapted MD definitions and practical guides is recommended.